Delivering Collaborative Web Labs as a Service for Engineering Education - Bochicchio, Mario A.; Longo, Antonella (International Journal of Online and Biomedical Engineering (iJOE), 2012)
As Internet speed grows up and academic networks reach more users, engineering schools take interest in online laboratories as a mean to increase the spectrum of offered services and to reduce costs by sharing expensive lab equipments. In this perspective, online labs must comply both with the scientific and pedagogic requirements coming from the lab users (students, researchers, â?¦) and with the requirements coming from the administrative and technical staff in charge to manage and deliver the lab services. In this paper we describe a system architecture based on both the classes of requirements and discuss the main results achieved implementing a prototype of the proposed architecture in a real academic scenario.